Strategi Pembelajaran Bahasa pada Kelas III di SD Negeri 02 Karangasem - Mohamad Sukron (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This article aims to understand how language learning in lower grade elementary schools, especially in grade II SD Negeri 02 Karangasem, covers aspects of reading, writing, listening, and speaking. Aspects of reading and writing are very important to be taught in elementary school. By reading and writing, all knowledge will be absorbed by students and they can understand and define the meaning of words that are read, heard, and remember them well. However, the difficulty in teaching beginning reading and writing lies in the strategies used. As for low grade students, learning should be a fun and meaningful activity. That is, activities that are close to the daily lives of students. Therefore, the strategies that can be applied are reading game learning strategies and early writing learning strategies using the SAS method. This strategy is based on student experience which is then applied in teaching reading and writing beginning to students.